Change of Threat Expectancy as Mechanism of Exposure-Based Psychotherapy for Anxiety Disorders: Evidence From 8, 484 Exposure Exercises of 605 Patients. (March 2023) - Pittig, Andre; Heinig, Ingmar; Goerigk, Stephan; Richter, Jan; Hollandt, Maike; Lueken, Ulrike; Pauli, Paul; Deckert, Jürgen; Kircher, Tilo; Straube, Benjamin; Neudeck, Peter; Koelkebeck, Katja; et al.
Individual responses to behavioral treatment of anxiety disorders vary considerably, which requires a better understanding of underlying processes. In this study, we examined the violation and change of threat beliefs during exposure. From 8, 484 standardized exposure records of 605 patients with different anxiety disorders, learning indicators were derived: expectancy violation as mismatch between threat expectancy before exposure and threat occurrence, expectancy change as difference between original and adjusted expectancy after exposure, and prediction-error learning rate as extent to which expectancy violation transferred into change. Throughout sessions, high threat expectancy but low occurrence and adjusted expectancy indicated successful violation and change of threat beliefs by exposure. Expectancy violation, change, and learning rate substantially varied between patients. Not expectancy violation itself, but higher learning rate and expectancy change predicted better treatment outcome. Successful exposure thus requires expectancy violation to induce actual expectancy change, supporting learning from prediction error as transdiagnostic mechanism underlying successful exposure therapy.